The meaning of place in the anthracite region of Northeastern Pennsylvania. Issue 3 (15th March 2016) - Shackel, Paul A.
Abstract: The Anthracite Heritage Project was founded to uncover one of the most tragic incidents in US labour history, the Lattimer Massacre. Initially, this work complemented the existing commemorative practices found in the anthracite coal region of Northeastern Pennsylvania. The various communities tend to remember a coal heritage that includes the story of migration, labour and survival. Recently, a new immigrant population has entered the region, and they are facing many of the prejudices and xenophobic fears that the European immigrants faced several generations ago. The history of the Lattimer Massacre, as well as other archaeological work that focuses explicitly on issues of immigration, has enabled the Anthracite Heritage Project to use and expand heritage to confront the racist tendencies found in the established community. The use of bridging social capital is one strategy being used to help better integrate the new population in this economically depressed area of Northern Appalachia.